Life satisfaction and internal migration experience: migrant workers in Guangzhou, China. Issue 3 (2nd September 2019) - Yue, Zhongshan; Fong, Eric; Yuan, Yue; Li, Shuzhuo
ABSTRACT: Our study links the life satisfaction of internal migrants with assessment of their migration outcomes in relation to the people back home and their integration experience. Our research adds to a growing body of literature on the integration of internal migrants in three ways. First, we extend the understanding of the subjective dimension of integration. Second, we have refined two important concepts for measuring migrant experience in our research. We differentiate local ties between local hukou and non-local hukou ties. Third, we provide a more comprehensive picture of life satisfaction among migrants by comparing relative importance of a set of variables. Data for this study come from a survey of rural–urban migrants in 2015–2016 in Guangzhou, China. The findings show that income, perceived socioeconomic status in comparison to that of local residents, perceived socioeconomic status in comparison to that of fellow villagers back home, and social ties with local hukou relative, and the perception of their own socioeconomic status have significant relationships with life satisfaction. Implications are discussed.